Virtual Reality As a Media For Introducing Minahasa Traditional Dances: Realitas Virtual Sebagai Media Pengenalan Tari Tradisional Minahasa - Akay, Yuri V. (Universitas Sam Ratulangi, 2025)
Traditional dance is an important part of cultural heritage that reflects the identity and values of the community. Minahasa has various traditional dances, such as the Kabasaran, Maengket, and Pisok dances, which are rich in philosophical and historical meaning. However, the younger generation's interest in traditional dances tends to decline due to the lack of interesting and interactive learning media. Virtual Reality (VR) technology offers an innovative solution in cultural preservation by creating an immersive experience that allows users to interact in a three-dimensional environment. This research aims to develop a Virtual Reality-based application as a medium for introducing Minahasan Traditional Dances so that it can be accessed anytime and anywhere. The system design method includes concept, design, material collection, assembly, testing, and distribution. The test results show that the VR application can run well on the device used and can display the dance stably. The result of this research is a Virtual Reality application that can introduce Minahasan dances and support the preservation of Minahasan culture. Keywords – Application; Android; Dances; Minahasa; Traditional; Virtual Reality. Tarian tradisional merupakan bagian penting dari warisan budaya yang merefleksikan identitas dan nilai masyarakat. Minahasa memiliki berbagai tarian tradisional, seperti Tari Kabasaran, Maengket, dan Pisok, yang sarat makna filosofis dan historis. Namun, minat generasi muda terhadap tarian tradisional cenderung menurun akibat kurangnya media pembelajaran yang menarik dan interaktif. Teknologi Virtual Reality (VR) menawarkan solusi inovatif dalam pelestarian budaya dengan menciptakan pengalaman imersif yang memungkinkan pengguna berinteraksi dalam lingkungan tiga dimensi. Penelitian ini bertujuan mengembangkan aplikasi berbasis Virtual Reality sebagai media pengenalan Tarian Tradisional Minahasa agar dapat diakses kapan saja dan di mana saja. Metode perancangan sistem meliputi konsep, perancangan, pengumpulan materi, pembuatan, pengujian, dan pendistribusian. Hasil uji coba menunjukkan bahwa aplikasi VR dapat berjalan dengan baik pada perangkat yang digunakan dan dapat menampilkan tarian secara stabil. Hasil dari penelitian ini adalah aplikasi Virtual Reality yang dapat mengenalkan tarian minahasa serta mendukung pelestarian budaya Minahasa. Kata kunci – Aplikasi; Android; Minahasa; Realitas Virtual; Tarian; Tradisional;